Keterlibatan Pemilik dalam Arah Kebijakan Keuangan untuk Mendorong Pertumbuhan Usaha Kecil dan Mikro di Wilayah Kabupaten Banyumas - Intan Shaferi; Muliasari Pinilih (Pro Bisnis, 2020)
This study aims to examine the influence of funding on the direction and growth of small and micro businesses. The study was conducted in the Banyumas district during the 2017 and 2018 periods or for two years. There are one hundred small and micro business data used in this study. Statistical analysis is used to test hypotheses. The results show that small and micro enterprises have adequate funding with the direction of external sources of funds used as part of an effort to obtain funds for business growth. So that the funding is important for business